Full factorial experimental design for mechanical properties of electrospun vascular grafts. (February 2018) - Enis, Ipek Y; Sezgin, Hande; Sadikoglu, Telem G
In this study, single layer vascular grafts were produced by a custom designed electrospinning apparatus. Both polymer type and rotational speed of the rotating collector were varied in single layer designs. Surface morphology of the fibrous scaffolds was observed under scanning electron microscope. Fiber diameter was measured and fiber orientation was analyzed by Image J Software. Scanning electron microscope images and fiber orientation analysis results indicated that fiber orientation was improved with increased rotational speed. Ultimate tensile strength and elongation at break values of the scaffolds were tested in planar forms. In addition to the experimental analysis, statistical analysis was also realized; 2 2 full factorial design was adapted to the test results in order to investigate the effect of polymer type and the rotational speed on elongation at break and ultimate tensile strength values. Results have shown that both polymer type and the rotational speed of the collector significantly influenced ultimate tensile strength and elongation at break values of scaffolds tested in the radial direction. When the scaffolds tested in the horizontal direction were considered, while both factors have had a poor effect on ultimate tensile strength, they were either significant or were very close to the confidence limits. On the other hand, the interaction effect of factors had a statistically significant influence on mechanical properties of both testing directions. The achieved results supported by statistical analysis can provide a reference for further studies in designing multilayer vascular grafts.